SCREENING PRESENCE AND ASSESSMENT OF SIZE NEUROPROTECTIVE EFFECT AMONG SOME DRUGS WITH ANTIOXIDANT ACTION OR MODULATING ACTIVITY ON FORMATION OF GLUTAMATE EXCITOTOXICITY AT IATROGENIC MODEL WITH COMPRESSION-TOXIC LESIONS INFERIOR ALVEOLAR NERVE IN RABBITS - Pogorila, A.V.; Шінкарук-Диковицька, М.М.; Khodakovsky, A.A. (World of Medicine and Biology, 2016)
In experiments on rabbits breed of Chinchilla in conditions iatrogenic compression-toxic damage the inferior alveolar nerve, modeled on the background of threaded putting into trepanation hole, which is located on the lower jaw in the projection of nerve, sealing materials based on resorcin-formaldehyde ( «Foredent»), or epoxy resin ( «AH-Plus»), established that neomidantan(10 mg / kg intragastric) as well as cerebrolysin, nucleo C.M.P. forte, berlithion doses of 2 ml / kg, 31.5 mg / kg and 1.2 ml / kg intravenous is carriers of neuroprotektors activity. The magnitude of the de-escalation of activity neuromarkers neuron-specific enolase (NSE), during the therapy of the iatrogenic compression-toxic lesions inferior alveolar nerve in rabbits by the neomidantan created a probably more neuroprotektions action compared to the same effect, which was implemented during treatment with other drugs. However , it can be concluded that the interruption of the primary reactions of glutamate-calcium cascade through the blockade of the excessive activity of NMDA-receptors, has advantages over the use of secondary neuroprotektors neurorestavration (cerebrolysin, nucleo C.M.P. forte) or metabolites-trophic orientation (berlithion) and this is a perspective for introduction in practical dentistry.